2013
DOI: 10.1021/am303149r
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties and Exciton Dynamics of Alloyed Core/Shell/Shell Cd1–xZnxSe/ZnSe/ZnS Quantum Dots

Abstract: In this study we introduce a new method for the one-pot synthesis of core/shell/shell alloyed Cd1-xZnxSe/ZnSe/ZnS QDs and examine the effect of the shell coating on the optical properties and exciton dynamics of the alloy core. The photoluminescence (PL) quantum yield is greatly enhanced after shell growth, from 9.6% to 63%. The exciton dynamics were studied by time correlated single photon counting (TCSPC) and fit using integrated singular value decomposition global fitting (i-SVD-GF), which showed the biexpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 35 publications
(66 reference statements)
5
59
0
Order By: Relevance
“…SVD global fitting [32][33][34] was also used to analyze the TA data for each of the four samples. Each contour plot, consisting of dA as a function of both delay time and wavelength, was fitted with three exponential lifetimes, which describe the decay of the TA signal over time for each wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…SVD global fitting [32][33][34] was also used to analyze the TA data for each of the four samples. Each contour plot, consisting of dA as a function of both delay time and wavelength, was fitted with three exponential lifetimes, which describe the decay of the TA signal over time for each wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Cation exchange was used to increase the bandgap and passivate trap states on the QD surface to increase PLQY. (De Trizio et al 2012;Fitzmorris et al 2013) By exchanging the surface copper and indium ions with zinc, the surface composition shifts to ZnS which facilitates the subsequent epitaxial growth of the ZnS shell (Van Embden et al 2007). The core CIS QDs were grown with an excess of the sulfur source, DPPS, which could allow some shell growth during the cation exchange step, although previous studies have shown that excess sulfur is not needed during cation exchange (Park and Kim 2011).…”
Section: Cation Exchange and Shell Growthmentioning
confidence: 99%
“…A good quality ZnS shell can be grown on the exposed CIS surfaces due to the small lattice mismatch between the two materials. ZnS shells have been shown to increase PLQY by passivating surface trap states on a range of QD systems including CdSe, CdZnSe, and CIS (Dabbousi et al 1997;Fitzmorris et al 2013;Li et al 2011;Park and Kim 2011;Speranskaya et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Smoothing of the interface in the heteronanocrystals by alloying can enhance the photoluminescence QY significantly due to swift variations in carrier‐confinement potential . As a result, the lattice strain at the interface is reduced significantly, along with a decrease in interfacial defects . The smooth nature of the alloy NC also allows an increase in the charge separation yield as compared with core–shell (type II) NCs with a sharper barrier at the interface.…”
Section: Introductionmentioning
confidence: 99%